Temperature, taphonomy, or technique? Contrasting hypotheses of ancient DNA recovery from Quaternary asphaltic fossil deposits - Robin R. Singleton; Kristen M. Rayfield; Karissa S. Hughes; Ezra M. Flint; Karin A. Rice; Laura R. Tewksbury; Sean C. Campbell; Aisling B. Farrell; John R. Southon; Emily L. Lindsey; Courtney A. Hofman; Alexis M. Mychajliw (Quaternary Science Reviews, 2026)

Corrigendum to “Temperature, taphonomy, or technique? Contrasting hypotheses of ancient DNA recovery from Quaternary asphaltic fossil deposits” [Quat. Sci. Rev. 389 (2026) 110106] - Robin Singleton; Kristen M. Rayfield; Karissa S. Hughes; Ezra M. Flint; Karin A. Rice; Laura R. Tewksbury; Sean C. Campbell; Aisling B. Farrell; John R. Southon; Emily L. Lindsey; Courtney A. Hofman; Alexis M. Mychajliw (Quaternary Science Reviews, 2026)

Heterogeneous distribution of surface hydrothermal alteration in the Nevados de Chillán Fractured Geothermal System, Southern Andes - Camila López-Contreras; Gloria Arancibia; Valentina Mura; Santiago Maza; Diego Morata; Philippe Robidoux; John Browning; David Healy; John Singleton (Geothermics, 2025)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

No effect on QT intervals of mipomersen, a 2′-O-methoxyethyl modified antisense oligonucleotide targeting ApoB-100 mRNA, in a phase I dose escalation placebo-controlled study, and confirmed by a thorough QT (tQT) study, in healthy subjects - Rosie Z. Yu; Rudy Gunawan; Zhaoyang Li; Robert S. Mittleman; Asif Mahmood; John S. Grundy; Walter Singleton; Richard Geary; Yanfeng Wang (European Journal of Clinical Pharmacology, 2016)

Connectivity Planning to Address Climate Change - TRISTAN A. NUÑEZ; JOSHUA J. LAWLER; BRAD H. MCRAE; D. JOHN PIERCE; MEADE B. KROSBY; DARREN M. KAVANAGH; PETER H. SINGLETON; JOSHUA J. TEWKSBURY (Conservation Biology, 2013)
As the climate changes, human land use may impede species from tracking areas with suitable climates. Maintaining connectivity between areas of different temperatures could allow organisms to move along temperature gradients and allow species to continue to occupy the same temperature space as the climate warms. We used a coarse‐filter approach to identify broad corridors for movement between areas where human influence is low while simultaneously routing the corridors along present‐day spatial gradients of temperature. We modified a cost–distance algorithm to model these corridors and tested the model with data on current land‐use and climate patterns in the Pacific Northwest of the United States. The resulting maps identified a network of patches and corridors across which species may move as climates change. The corridors are likely to be robust to uncertainty in the magnitude and direction of future climate change because they are derived from gradients and land‐use patterns. The assumptions we applied in our model simplified the stability of temperature gradients and species responses to climate change and land use, but the model is flexible enough to be tailored to specific regions by incorporating other climate variables or movement costs. When used at appropriate resolutions, our approach may be of value to local, regional, and continental conservation initiatives seeking to promote species movements in a changing climate. Planificación de Conectividad para Atender el Cambio Climático